Effects of Rotation with Trap Crops on Striga (Striga hermonthica Del. Benth) Incidence, its Seed Bank and Sorghum Growth and Yield - Elneel, Ahmed H. Hamad; Hamid, Sami A.; Babiker, Abdelgabar T. (University of Khartoum Journal of Agricultural Sciences, 2023)
A trial was conducted for three consecutive seasons (2006/07, 2007/08 and 2008/09) in a field artificially infested by Striga hermonthica in the Experimental Farm of the Faculty of Agriculture, University of Sinnar. The effects of a two seasons’ crop rotation on striga incidence, its seed bank and growth and yield of subsequent sorghum crop were investigated. The rotation comprised the trap crops, cowpea (Vigna unguiculata), millet (Pennisetum glaucum), sesame (Sesamum indicum), sunflower (Helianthus annuus) and fallows, in assorted combinations. A sorghum monoculture, for the three seasons, was included as a control. All treatments reduced striga emergence significantly in comparison to sorghum monoculture. Sunflower and sesame grown for two consecutive seasons caused the maximum reductions (80%), while a fallow followed by sorghum resulted in the least reduction (42%). Significant reduction in striga capsules (37%) was caused by two consecutive sesame crops. In the second season, all treatments significantly reduced striga seed bank,. Two consecutive fallows and two consecutive crops each of cowpea, millet and sunflower resulted in the highest reductions in striga incidence (80% - 92%), while a fallow followed by sorghum exhibited the least reduction (51-65%). None of the treatments had adverse effects on sorghum stand early in the season; however, at harvest significant reduction was observed. Sorghum monoculture resulted in the lowest stand, while sunflower planted subsequent to a fallow and two successive sunflower crops affected the highest stands. Among all treatments, sorghum